Strategies and performances of Functional Electrical Stimulation Cycling using the BerkelBike with Spinal Cord Injury in a competition context (CYBATHLON) - Rik Berkelmans; Billy Woods (PAGEPress Publications, 2017)
The functional electrical stimulation (FES) bicycle race was an event at the Cybathlon, held in Zurich October 2016. BerkelBike BV (The Netherlands) in collaboration with Imperial College London entered a spinal cord injury pilot who had tetraplegia to compete in this event. The BerkelBike Pro is a commercially available FES capable recumbent which is normally driven by the arm- and leg power. The arm cranking part was disabled. Now the tricycle must be driven using the pilots own lower limb muscles through stimulation in accordance with race rules. The bike used during the race was also adapted with a fixed gear for improved efficiency. The pilot who represented this team come second place overall in the event and attained the fastest race time of all pilots who utilised surface electrode FES. Steps can be taken to increase the race efficiency of the BerkelBikes and its FES capabilities even further.